Age-related differences in borderline personality disorder traits and childhood maltreatment: a cross-sectional study - GuoRong Li; Yong Lin; Yun Xu; Yong Zhou; YanYan Wei; LiHua Xu; XiaoChen Tang; Zixuan Wang; Qiang Hu; JiJun Wang; HaiSu Wu; ZhengHui Yi; et al. (Frontiers in Psychiatry)
IntroductionThis study investigates age-related differences in Borderline Personality Disorder (BPD) traits and childhood maltreatment (CM) experiences among adolescents, young adults, and older adults within a clinical sample.MethodsA cross-sectional design was employed, involving 2029 outpatients aged 15-50 years from the Shanghai Mental Health Center. BPD traits were assessed using the Personality Diagnostic Questionnaire 4th Edition Plus (PDQ-4+), and CM experiences were evaluated using the Child Trauma Questionnaire Short Form (CTQ-SF). Participants were categorized into three age groups: adolescents (15-21 years), young adults (22-30 years), and older adults (31-50 years).ResultsAdolescents reported significantly higher frequencies of BPD traits and diagnoses compared to young adults and older adults (p=0.036). Specifically, identity disturbance and impulsivity were more pronounced in adolescents (p<0.001). Additionally, adolescents reported higher levels of emotional (F=15.987, p<0.001) and physical abuse (F=12.942, p=0.002), while older adults reported higher levels of emotional and physical neglect. Logistic regression analysis identified key BPD criteria and CM subtypes that differentiated adolescents from adults.DiscussionThe findings underscore the importance of age-specific interventions in treating BPD and addressing childhood maltreatment. Adolescents exhibit distinct patterns of BPD traits and CM experiences, necessitating tailored therapeutic approaches.